RETRIEVAL OF SOLITON SOLUTIONS OF (1+1)-DIMENSIONAL NON-LINEAR TELEGRAPH EQUATION - Das, Sebahat Ebru (VINCA INST NUCLEAR SCI, 2022)
In this work, we aim to determine the possible soliton solutions and examine the behaviors of the (1+1)-dimensional non-linear Telegraph equation (NTE) which is used to model signal processing for the propagation of transmission of the electric impulses and also wave theory process by using the extended Kudryashov method. We started by finding the non-linear ordinary differential form of the (1+1)-NTE with the aid of a suitable wave transformation. Then, the extended Kudryashov method approach has been demonstrated and implemented to the obtained non-linear ordinary differential form. As a result, a polynomial expression has been achieved and converted to a linear algebraic equation system. Soliton solutions of the investigated equation are produced by solving the system and choosing the appropriate solution sets. Finally, graphical depictions, gained results and necessary comments are given.
Keywords: electrical transmission; soliton solution; wave transform; electric impulse; TRAVELING-WAVE SOLUTIONS; (G'/G)-EXPANSION METHOD; EVOLUTION-EQUATIONS; OPTICAL SOLITONS; Thermodynamics